Multi-layer Modeling of Bifacial Photovoltaic Panels: Evaluating the Accuracy of One-, Three-, and Five-layer Models - Mohammad Hassan Shahverdian; Hoseyn Sayyaadi; Ali Sohani (Energy Conversion and Management: X)
Bifacial solar panels (BSP) absorb sunlight from both sides. BSP has gained significant popularity by increasing energy efficiency and reducing the need for more space. To predict the performance of BSP, it is necessary to perform three analyzes, optical, thermal, and electrical simultaneously, because the power generated is influenced by the surface temperature and vice versa. For the thermal modeling of the BSP, the solar panel can be examined in different layers. In this study, thermal modeling is conducted in the one, three-, and five-layer models, and these models are compared with each other from the point of view of produced power and panel temperature to determine the accuracy of each approach. A BSP is considered in the climatic conditions of Tehran, Iran. Finally, the result was obtained that in the annual analysis, the amount of energy produced by the five, three, and one-layer models is 1242.2, 1244.0, and 1246.6 kWh, respectively. The variation between the five-layer and one-layer model is 0.36 %, between the three-layer and one-layer is 0.21 %, and between the five-layer and three-layer is 0.15 %. As a result, considering the model with more layers, does not necessarily increase the accuracy of the analysis, significantly.